1996
DOI: 10.1037/0735-7044.110.6.1496
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the lateral parabrachial nucleus block the aversive motivational effects of both morphine and morphine withdrawal but spare morphine's discrimination properties.

Abstract: This study examined if the aversive properties of morphine, the aversive properties of morphine withdrawal, and the discriminative properties of morphine are mediated by common neurobiological substrates. Lesions of the lateral parabrachial nucleus, which blocked the aversive properties of morphine in the conditioned taste aversion paradigm, also blocked the acquisition of conditioned place aversions to environments paired with the aversive properties of morphine withdrawal in morphine-dependent rats. When mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In relation to the CPA, these results are compatible with previous reports that the parabrachial complex as a whole is related to aversive processes (Bernard et al 1994, Nader et al 1996, Mediavilla et al 2000. More specifically, it has been suggested that the NLPBe may play a major role in processing the affective and emotional components of nociception (Gariau and Bernard 2001) or taste (Hajnal and Norgren 2004) and even in generating human feelings of wellbeing or malaise (Balaban andThayer 2001, Schachter 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In relation to the CPA, these results are compatible with previous reports that the parabrachial complex as a whole is related to aversive processes (Bernard et al 1994, Nader et al 1996, Mediavilla et al 2000. More specifically, it has been suggested that the NLPBe may play a major role in processing the affective and emotional components of nociception (Gariau and Bernard 2001) or taste (Hajnal and Norgren 2004) and even in generating human feelings of wellbeing or malaise (Balaban andThayer 2001, Schachter 2004).…”
Section: Discussionsupporting
confidence: 90%
“…The parabrachial complex has been related to both rewarding and aversive behavioral processes. Its involvement has been reported in taste aversion learning (Mediavilla et al 2005, Carter et al 2015, the processing of affective and autonomic dimensions of pain (Gauriau and Bernard 2002), the aversive effects of some drugs of abuse (Nader et al 1996), and in the effects induced by administration of various rewarding nutrients (Yamamoto and Sawa 2000a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Our results reveal that non-dependent versus post-dependent states influence the regulation of opiate reward by the orexin system. Previous studies (Bechara et al, 1992; Bechara et al, 1995; Nader and van der Kooy, 1996, 1997) support the idea of a state-dependent difference in brain regions required for opiate reward, such that a dopamine neurons are needed in animals with previous drug exposure whereas a non-dopaminergic system is required in naïve animals (Bechara et al, 1995). Although there was no significant difference in preference scores for post- and non-dependent rats in our study, in contrast with other studies (Harris et al, 2003a, 2006), our current finding was consistent with a previous report (Bechara et al, 1992).…”
Section: Discussionmentioning
confidence: 81%
“…Overall, nicotine-treated rats expressed significantly more withdrawal signs at 6, 12 and 24 h post-pump removal compared to saline-treated rats; *p < 0.05, significantly different from age appropriate saline-treated rats. c Bars represent mean (+SEM) time spent in the withdrawal-paired (black bars) and non-withdrawal-paired (white bars) compartments during the 15-min place aversion test, n=12 per group controlled studies have argued against this possibility (Nader et al 1996;Bechara et al 1998;Grieder et al 2007). It remains possible that other procedures are more sensitive in detecting withdrawal responses, particularly when considering the milder nature of withdrawal from nicotine compared to other drugs of abuse.…”
Section: Time Spent In Compartment (Sec)mentioning
confidence: 97%